DIMENSI KRITIS PEMIKIRAN AKUNTANSI YANG TERALIENASI: DIALOG IMAJINER KONSTRUKSIONIS DAN DEKONSTRUKSIONIS - Akhmad Riduwan; Andayani Andayani (Media Riset Akuntansi, Auditing & Informasi, 2019)
This article aims to: (1) elevate the critical dimension of accounting thoughts which is alienated and repressed by dominant mainstream thought; and (2) build awareness of accounting academics and practitioners that (a) financial accounting can not only be developed by reflecting on economic and financial theories but can also be developed by reflecting on critical theories of sociology; and (b) accountants are not "one-dimension man", but persons who are able to perceiving and discovering the reality of their profession from various dimensions critically.This article are prepared based on literature review. The literature of accounting practices and financial reporting is exploited along with the exploration of the underlying critical thoughts. To achieve the objectives of the study, the conceptual framework of financial reporting is examined from a constructionist and deconstructionist perspective. The study was conducted contemplatively on the basis of critical sociological theory. The results of the study from the constructionist and deconstructionist perspective are presented in an imaginary-contemplative dialogue format.The results of the review indicate that: (1) the critical dimension of accounting thought needs to be raised in the effort to develop the concept and practice of financial reporting, so that it can become alternative thinking without destructing mainstream thinking; (2) ongoing financial reporting concepts and practices can not only be evaluated by reflecting on the parent theory of accounting discipline (i.e. economics and finance), but can also be evaluated by reflecting on the critical sociology theories relevant to the context. This builds awareness that accounting practices actually evolve in line with the development of human civilization, and accounting also has an important role to play in the development of that civilization; (3) the development of financial reporting concepts and practices should not be based on the economic and financial interests of the reporting entity, but must also be based on the public interest in general. This means that accountants are not supposed to be "one-dimension man", but become individuals who are able to find their profession in critical dimensions.